Infrared Laser Effects on Cell Projection Depend on Irradiation Intermittence and Cell Activity - Norma Medina-Villalobos; Remy Avila; María Marsal; Jordi Andilla; Pablo Loza-Álvarez; Mario Miguel Ojeda-Ramírez; Elisa Tamariz (Cells, 2023)
Highly focused near-infrared (NIR) lasers have been used to induce fibroblast and neuron protrusions in a technique called optical guidance. However, little is known about the biochemical and biophysical effects that the laser provokes in the cell and optimal protocols of stimulation have not yet been established. Using intermittent NIR laser radiation and multivariate time series representations of cell leading edge movement, we analyzed the direction and velocity of cell protrusions. We found that the orientation and advance of PC12 neuron phenotype cells and 3T3 fibroblasts protrusions remain after the laser is turned off, but the observed increase in velocity stops when radiation ceases. For an increase in the speed and distance of cell protrusions by NIR laser irradiation, the cell leading edge needs to be advancing prior to the stimulation, and NIR irradiation does not enable the cell to switch between retracting and advancing states. Using timelapse imaging of actin-GFP, we observed that NIR irradiation induces a faster recruitment of actin, promoting filament formation at the induced cell protrusions. These results provide fresh evidence to understand the phenomenon of the optical guidance of cell protrusions.